Relationship between the shape of the upper central incisors and the facial contour in dental students. Lima. Peru. - Miguel Cabello; Sergio Alvarado (Universidad de Concepción., 2015)
Determine the relationship between the shape of the face and the shape of the upper right central incisor according to "The law of harmony" proposed by Williams. Materials and methods: This was an observational, analytic and cross-sectional study. A sample of 124 subjects, male and female students between 17 and 28 years old, was selected for the research. Their facial biotype and the shape of their upper right central incisor were determined by means of direct and photographic methods. Height and facial width were clinically evaluated using the direct method, and the proximal contours of the incisors were evaluated using a Vernier digital caliper. Images were downloaded to a computer and analyzed by means of the photographic method using Adobe Photoshop 5.0. Results: The relationship between the shape of the face and the shape of the incisor was positive in 43.5% of the sample (p=0.006) in the direct method. In the photographic method, the relationship between the shape of the face and the shape of the incisor was positive in 41.1% of the sample (p=0.037). The most frequent facial biotype in the direct and photographic methods was the dolichofacial with 61.3% and 71% respectively. The most frequent shape of the tooth with the direct and photographic methods was the ovoid with 55.6% and 51.6% respectively. Conclusion: Results do not confirm "The law of harmony" proposed by Williams, therefore when choosing the most suitable anterior tooth, experience and criteria of the dentist as well as the opinion of the patient should be taken in account in order to achieve a good aesthetic result.